KAZAKH TRADITIONAL MUSIC IN THE CONTEXT OF GLOBAL GENRES-STYLISTIC TRENDS IN MUSICOLOGY - Aіnur Zhasaganbergenovna Kaztuganova (Progress in Science, 2024)
At the end of the twentieth and twenty-first centuries, especially over the last 10 years, computer technologies, Internet sites, mass media (radio, television, newspapers, magazines) actively penetrated into the life of society, contributing to the public consciousness. Consequently, various phenomena related to the era of globalization have influenced the genres of traditional musical culture. The development of society is constantly striving for new things, in this regard, it is necessary to note the processes of synthesis in traditional music. Through this, new concepts, trends, styles and genres are defined in musicology.